Comparison of The Concept of Halal Products in Unusa Nutrition Students and Unusa Outside Nutrition Students in Surabaya - Yanuar Dini, Cleonara; Setiarsih, Dini (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Indonesia is a country with the largest Muslim population, so the majority of Muslims are very concerned about the halal food they consume. However, the existing halal food is not necessarily in line with the Muslim population. Therefore, there is significant data in research on consumer behavior in consuming halal food. Related studies or literature especially regarding the role of religion on consumer behavior is still minimal. Thus, this research is expected to be useful for students, both consumers and producers, as well as the government and other related parties as a reference in formulating policies related to halal industrial production, especially processed food products. This paper mainly aims to examine the comparison of Muslim consumer behavior towards halal products that are in the majority and Muslim minorities, in terms of determinant factors. Data processing techniques include quantitative and qualitative analysis data obtained in 2020 from UNUSA Nutrition Students and Non-UNUSA Nutrition Students.